They just don’t get it! Towards informing course and syllabus design – an error analysis of referencing in undergraduate writing - Van Dyk, Tobie; Andrianatos , Kristien (Journal for Language Teaching, 2022)
For students to formulate a well-supported academic argument, proper source integration skills need to be applied. This depends on a student’s ability to quote or paraphrase sources and adhere to referencing styles’ technical requirements. Academic writing teachers need to investigate which aspects of source integration students fail to master. By utilising the multilevel, multi-genre, multi-language learner corpus of South African languages for academic purposes compiled on behalf of the South African Centre for Digital Language Resources (SADiLaR), we performed an error analysis of typical referencing errors and the frequency of specific kinds of referencing errors in the academic writing of first-year students. This error analysis enabled us to move beyond “having an idea of what errors they make”, to an in-depth investigation of recurring errors, in order to be able to offer focused academic writing support. Findings include, firstly, consistently recurring technical errors with citation format. Secondly, students struggle with formatting reference lists as per the required referencing style. With this paper, we wish to initiate a discussion on the importance of teaching the mechanics of referencing and other pedagogical inferences to inform course and syllabus design, focused on source integration.